Analysis of Religious Court Decisions in Resolving Inheritance Disputes Still Under Collateral a Maqashid Syariah Perspective - Yusep Abdulsiddik; Utari Roza Elsera; Alfi Husni (Hakamain: Journal of Sharia and Law Studies, 2024)
Inheritance law governs the transfer of wealth left by a deceased person and its impact on the heirs. Issues often arise regarding the management and continuation of the rights and obligations of the deceased. This study aims to describe inheritance cases still under collateral at the Religious Court of Talu and to analyze the judicial decision from the perspective of Maqashid Syariah. The study employs two approaches: the statute approach and the analytical approach. The research findings show that the judge granted the inheritance dispute still under collateral with case registration number 559/Pdt.G/2022/PA.Talu. This was due to the judge's application of "rule-breaking," meaning the judge bypassed positive legal rules or written law that were deemed unjust for the seeker of justice. From the perspective of Maqashid Syariah, this decision falls under the category of hajiyyah in the aspect of hifdz mal, meaning that while the need may not result in harm if unmet, it can create various difficulties. Inheritance assets should ideally be distributed promptly to avoid delay and be given to the rightful heirs. In this context, postponing the distribution until the collateral obligations are resolved serves to provide certainty, justice, and prevent potential conflicts among heirs. Thus, the decision aligns with the objectives of Islamic law, which aim to bring benefit and prevent harm.